Dampak Pembangunan Tol Trans Jawa terhadap Pertumbuhan Ekonomi Kabupaten Mojokerto, Jombang, Kediri, dan Nganjuk - Ahmad Reza Rokhmanto (LPPM STIE EKA PRASETYA, 2024)
This study aims to analyze the influence of toll roads on economic growth and the potential sectoral transformations in the research region. The research employs a panel data analysis method with a quantitative approach. The study was conducted in four regencies in East Java, namely Nganjuk Regency, Kediri Regency, Jombang Regency, and Mojokerto Regency. The research results indicate that the partial effect of toll road development does not have a significant impact on economic growth. However, when considered simultaneously with the Human Development Index variable, it shows a significant influence on economic growth.